Pendalaman Kitab Suci Sebagai Media Untuk Menyadari Allah Sumber Kasih Dan Keselamatan - Stanislaus Efodius Harmansi; Yosefina Jaiman; Hilaria Juita; Margareta Sonia Dini; Paulus Darma (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This article describes the community service (Pengabdian kepada Masyarakat, PkM) of the Theological Education Study Program of the Indonesian Catholic University of Saint Paul Ruteng. The target group is the people at Christ the Redeemer Parish, Rentung. This parish is included in the ecclesiastical administrative area of the Ruteng Diocese. It was found that there was a lack of interest among people in reading the Holy Bible in the Ruteng Diocese. To face this problem, efforts are needed to study the Holy Scriptures. The aim of PkM is to help people read and reflect on the Word of God in the Holy Bible and discover values that lead them to an awareness of God as the source of love and salvation. As a result, through sharing and prayer, the people's awareness of God, the source of love and salvation, is revealed.